Synotis lhozhagensis (Asteraceae, Senecioneae), a new species from south-eastern Xizang, China, based on morphological and molecular evidence - Guo-Xing Peng; Liao-Cheng Zhao; Ming Tang; Jun Deng; Hao-Ming Zhan; Zhuo-Ni Zhang; Qiang Wang (PhytoKeys)
Synotis lhozhagensis, a new species belonging to Senecioneae (Asteraceae), is described and illustrated herein after being discovered during biodiversity surveys in Lhozhag County, Xizang Autonomous Region, China. This species is similar to S. acuminata (Wall. ex DC.) C.Jeffrey & Y.L.Chen, but differs mainly in having the ray floret absent (vs. 1), the leaf margins irregularly coarsely serrate (vs. finely mucronulate-serrate) and the phyllaries five (vs. three or four). It is also allied to S. glomerata C.Jeffrey & Y.L.Chen in growth habit, leaf blade morphology and inflorescence structure, but is distinguished by the corymbs loose and spreading (vs. dense and glomeruliform), the ligulate floret absent (vs. one or two) and the disc florets five (vs. three or four). Phylogenetic analysis, based on ITS sequences, confirms its distinct taxonomic status within Synotis. A line drawing and colour plates, a geographic distribution map, a detailed comparison table including the aforementioned three species and the provisional IUCN status are provided.